An analysis of the effectiveness of using Ex-combatants as agents of peace: A case of ZPRA Veterans Trust from 2009 to 2014 - Mafu, Philasande (2017)
Globalization and the continued interdependencies in the international arena have intensified the growth and status of non-governmental organizations in the 21st century. Funded by great powers these NGOs have taken part as the leading practitioners of development in Africa. However, such measures are posing threats to the power and sovereignty of African governments, resulting in these States’s obscurely reactions and labeling of NGOs as agents of imperialism. As a result, the existence and survival of NGOs has become hard-edged in political sensitive States like Zimbabwe. With special attention to peace-building NGOs, this dissertation therefore, explores government-NGO relations and its effects on promotion of national healing, reconciliation and peace-building in Zimbabwe. Thus, despite the harsh fabricated laws governing NGOs in Zimbabwe, ZPRA Veterans Trust (formed by Ex-combatants), has seen the necessity and need for peace-building in the country, based on the reality that people of Zimbabwe have been abused by the political instabilities and crises wandering the country since colonization until 2008 elections, leaving grave traumas, conflicts and disunity among Zimbabweans. This research therefore, seeks to reveal the unseen potential possessed by Ex-combatants that could make them best agents of peace, through examining survival strategies of ZPRA Veterans Trust, its challenges and most importantly the effectiveness of its programs.